1H NMR-based metabolomics and sensory evaluation characterize taste substances of Jinhua ham with traditional and modern processing procedures. (August 2021) - Zhou, Chang-Yu; Bai, Yun; Wang, Chong; Li, Chun-Bao; Xu, Xing-Lian; Pan, Dao-Dong; Cao, Jin-Xuan; Zhou, Guang-Hong
Abstract: Jinhua ham is one of high quality dry-cured products, and processing methods play a key role in developing the taste attributes of Jinhua ham. To investigate the effect of processing methods on sensory attributes and taste substances of Jinhua ham, this work highlighted the changes of sensory characteristics, texture parameters, water distribution and metabolite profiles, and further discussed the contribution of metabolites to the development of taste and richness in both traditional-processed and modern-processed hams. The modern-processed hams showed higher taste scores and richness intensities than that of traditional processing. The populations of immobilized water significantly increased from raw ham to the later stage of dry-ripening, accompanied by a decrease in the populations of free water during the processing of traditional and modern procedures, while higher populations (more than 2-fold) of free water were shown in the ham of modern processing at the end of post-ripening compared with traditional-processed ham. 1H NMR-based metabolomics revealed that free amino acids, small peptides and organic acids were the most intense response in developing taste and richness intensities of modern-processed ham. Partial least square discriminant analysis and taste-active values further demonstrated that glutamic acid, lactate, glycerol, anserine and creatine were responsible for the higher taste and richness intensities of modern-processed ham. Graphical abstract: Image 1 Highlights: Metabolites were evaluated in Jinhua ham with modern and traditional processing. The shift of free water to immobilized water developed the texture of Jinhua ham. Higher taste and richness intensities were shown in modern-processed Jinhua ham. Free amino acid, small peptide and organic acid improved the taste of Jinhua ham.